UNVEILING COHERENCE: ANALYZING GRAMMATICAL DEVICES IN RECOUNT TEXT - Dewi Nurpitriyani; Didin Nuruddin Hidayat; Nida Husna; Alek Alek (University of Kuningan, 2023)
The purpose of this study is to examine the grammatical cohesive devices used in the recount text writing of bilingual students. The cohesive device is crucial because it consists of grammatical and lexical devices that contribute to the writing’s strength and accuracy, as well as its contextual understanding. Twenty bilingual ninth-grade students of a junior high school participated in this study. The students’ recount text writings were used as the main data in this research. The qualitative descriptive method employed in this study to thoroughly assess and describe students’ writing and its’ cohesive device used. The result shows that the bilingual ninth-grade students were able to use grammatical cohesion in their recount text writing. The result revealed the reference is most dominated in 68.42% and the second device is in conjunction with 29.97%. Meanwhile, substitution showed the low rank with 1.61% and the last was ellipsis with 0%. Furthermore, in the reference device category, personal reference becomes the most highly used at 85%, meanwhile in the conjunction category, additive category becomes the most frequent one at 46% as well as nominal substitution at 50% in the substitution device. It was also found that the ninth-grade students of bilingual class can write well using numbers of grammatical cohesive devices even though there was still some monotonous repetition in their writing. he findings of this study have pedagogical implicature as the need to enhance students’ knowledge of grammatical cohesion device because understanding of cohesiveness is necessary for pertaining to the text’s cohesion and coherence particularly in writing ability.